Non-invasive imaging techniques for early diagnosis of bilateral cardiac dysfunction in pulmonary hypertension: current crests, future peaks - Ahmad, Ashfaq; Zou, Yifan; Zhang, Peng; Li, Lingling; Wang, Xiaoyu; Wang, Yousen; Fan, Fenling (Frontiers in Cardiovascular Medicine, 2024)
Pulmonary arterial hypertension (PAH) is a chronic and progressive disease that eventually leads to heart failure (HF) and eventual fatality if left untreated. Right ventricular (RV) function has proven prognostic values in patients with a variety of heart diseases including PAH. PAH is predominantly a right heart disease, however, given the nature of the continuous circulatory system and the presence of shared septum and pericardial constraints, the interdependence of the right and left ventricles is a factor that requires consideration. Accurate and timely assessment of ventricular function is very important in the management of PAH patients for disease outcomes and prognosis.Non-invasive modalities such as cardiac magnetic resonance (CMR) and echocardiography (two-dimensional and three-dimensional), Nuclear Medicine, positron emission tomography (PET), etc. play a crucial role in the assessment of ventricular function and disease prognosis. Each modality has its own strengths and limitations hence this review article sheds light on (i) ventricular dysfunction in patients with PAH and RV-LV interdependence in such patients, (ii) the strengths and limitations of all available modalities and parameters for the early assessment of ventricular function, as well as their prognostic value and (iii) lastly the faced challenges and potential future advancement in these modalities for accurate and early diagnosis of ventricular function in PAH.